Risk of liver dysfunction and non-alcoholic fatty liver diseases in people with hidradenitis suppurativa: A systematic review and meta-analysis of real-world evidences - Gau, Shuo-Yan; Hsiao, Yu-Ping; Liao, Wen-Chieh; Ma, Kevin Sheng-Kai; Wu, Meng-Che (Frontiers in Immunology, 2022)
Abstract Background To date, evidences with high evidence-level evaluating the association between liver diseases and hidradenitis suppurativa was lacking. Given that inconsistency exists in some of the previous observational studies, evaluating the prevalence of liver diseases in HS patients could potentially serve as a reference of future guidelines for HS comorbidity screening. The aim of the current study was to evaluate potential association between hidradenitis suppurativa and liver diseases and provide integrated evidences. Methods A search in PubMed, Web of Science and Embase based on the syntaxes ‘‘hidradenitis suppurativa’’ or ‘‘acne inversa’’ with “comorbidities”, “liver diseases”, “fatty liver” or “hepatitis” was performed. Observational studies evaluating epidemiological association between hidradenitis suppurativa and the risk of all liver diseases, including specific diseases as non-alcoholic fatty liver disease, hepatitis B, hepatitis C were targeted to be extracted in this systematic review and meta-analysis. Results Within the initial 702 records, there were finally 8 real-world observational studies extracted. Results suggest that patients with HS are associated with all liver diseases (OR= 1.50; 95% CI, 1.27, 1.76), non-alcoholic fatty liver disease (OR= 1.78; 95% CI, 1.28, 2.48) and hepatitis B (OR=1.48; 95% CI, 1.12, 1.94), but not hepatitis C (OR= 1.27; 95% CI, 0.78, 2.07). HS patients were associated with significantly increased risk of liver diseases, especially the risk of non-alcoholic fatty liver disease and hepatitis B. Conclusions Clinicians should be alert to the clinical relationship while caring people with hidradenitis suppurativa and the screening of liver function should be recommended to HS patients.